2017
DOI: 10.1017/s1759078716001410
|View full text |Cite
|
Sign up to set email alerts
|

X-band compact dual circularly polarized isoflux antenna for nanosatellite applications

Abstract: International audience— This paper presents an original solution to design a compact dual circularly polarized isoflux antenna (DCPIA) for nanosatellite applications. This kind of antenna has been previously designed in our laboratory, for a single circular polarization. This antenna is composed of a dual circularly polarized feed and a choke horn antenna. This feed is a cross-shaped slot in the ground plane which provides coupling between a patch and a ring microstrip line with two ports. It is located at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Moreover, this antenna showed return loss values of −18.5 dB, a bandwidth of 163 MHz, and a gain of 6.08 dB. Concerning the X band, a design for a compact antenna for isoflux radiation with circular polarization operating in the X band (8–8.4 GHz) was presented in [ 28 ]. Moreover, an array of 25 elements operating in the central frequency of 8.2 GHz with a realized gain of −10 dB was proposed in [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this antenna showed return loss values of −18.5 dB, a bandwidth of 163 MHz, and a gain of 6.08 dB. Concerning the X band, a design for a compact antenna for isoflux radiation with circular polarization operating in the X band (8–8.4 GHz) was presented in [ 28 ]. Moreover, an array of 25 elements operating in the central frequency of 8.2 GHz with a realized gain of −10 dB was proposed in [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most straightforward approach is to excite the microstrip antenna (MSA) by means of two distinct and spatially orthogonal feeds with a phase‐difference of 90° between them as reported in References . However, in these works, either the antenna has a large electrical size, or the AR bandwidth is low, or the antenna suffers from narrow impedance bandwidth . The linearly polarized MIMO antenna in Reference has a meander line resonator used to reduce the coupling between antenna ports.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we propose a DCP FDX slot antenna with high inter-port isolation and wider impedance and axial ratio (AR) bandwidth compared to contemporary designs. [4][5][6][7] This design incorporates the approach presented in Reference 7, where it was shown that the inter-port isolation may be enhanced by introducing a net negative admittance of −jβ to cancel out the residual signal between the T X and R X ports. The designed antenna has two "8" shaped slots inclined at 135 and 45 to the horizontal axis for R X and T X operations respectively.…”
Section: Introductionmentioning
confidence: 99%
“…According to these requirements, various structures have been developed and investigated. Some practical antennas such as cross dipoles [4], bifilar helixes [6,7], quadrifilar helixes [8], conical spirals [9] and isoflux antennas [10] have been investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%